An ornithological survey in north-east India - Birand,A; Pawar,S (Forktail, 2004)
We conducted surveys between October 2000 and June 2001 at nine sites in north-east India with low- to mid-elevation tropical evergreen forest, with a particular focus on forest species. 261 bird species were recorded, including five globally threatened species (White-winged Duck Cairina scutulata, Rufous-necked Hornbill Aceros nipalensis, Pallas’s Fish Eagle Haliaeetus leucoryphus, Lesser Adjutant Leptoptilos javanicus, Beautiful Nuthatch Sitta formosa, four Near Threatened species (White-cheeked Partridge Arborophila atrogularis, Great Hornbill Buceros bicornis, Brown Hornbill Anorrhinus tickelli, Blyth’s Kingfisher Alcedo hercules), three restricted-range species, several poorly known species, and a number of new altitudinalrecords. In general, north-east India remains deficient in avifaunal data. Further surveys, especially in the poorly known interior montane tracts, are needed to assist the identification of conservation priorities in the region.